Analysis of genomic and characterization features of Luteolibacter soli sp. nov., isolated from soil - An, Jing; Xuan, Xiaoqi; Wang, Yanan; Wu, Linwei; Zhou, Jizhong; Mu, Dashuai (Frontiers in Microbiology, 2024)
The strain designated as Y139T is a novel Gram-stain-negative, aerobic, and non-motile bacterium, was isolated from a soil sample in McClain County, Oklahoma, USA. The cells of strain Y139T were a rod-shaped, with the width of 0.4–0.7 μm and the length of 1.5–2.0 μm. Growth occurred at 20–37℃ (optimum, 30℃), pH 5.5–9.5 (optimum, pH 7.0), and 0–1.0% NaCl (w/v) (optimum, 0%). The polar lipid profiles included phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, phosphatidyldimethylethanolamine, and an unidentified lipid. The major fatty acids included C16:0, iso-C14:0, and C16:1 ω9c. Menaquinone-9 (MK-9) was recognized as the only respiratory quinone. Strain Y139T showed the highest 16S rRNA gene sequence similarity to Luteolibacter flavescens MCCC 1K03193T (98.3%). Phylogenetic analysis positioned it within the genus Luteolibacter. The draft genome of strain Y139T consisted of 7,106,054 bp, and contained 5,715 open reading frames (ORFs), including 5,656 coding sequences (CDSs) and 59 RNA genes. The genomic DNA G+C content was found to be 62.5%. Comparing strain Y139T with L. flavescens MCCC 1K03193T and Luteolibacter arcticus CCTCC AB 2014275T, the average nucleotide identity (ANI) values were 80.6 and 82.1%, respectively. Following phylogenetic, physiological, biochemical, and chemotaxonomic analyses, a novel species within the genus Luteolibacter, designated as Luteolibacter soli sp. nov., was proposed for strain Y139T, which was also assigned as the type strain (=KCTC 92644T =MCCC 1H01451T). Further analysis of core genes across 9 Luteolibacter species uncovered significant genomic divergence, particularly in those related to cofactor, vitamin, and energy metabolism. Analysis of biogeographic distribution suggested that lake and soil were the main habitats for the genus Luteolibacter. Additionally, the genus Luteolibacter was sensitive to climate warming and precipitation.